2012
DOI: 10.1093/jnci/djr530
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Multilingual Telephone Quitline for Asian Smokers: A Randomized Controlled Trial

Abstract: Telephone counseling was effective for Chinese-, Korean-, and Vietnamese-speaking smokers. This protocol should be incorporated into existing quitlines, with possible extension to other Asian languages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 32 publications
1
75
2
Order By: Relevance
“…38,40 The abstinence rates obtained from this pilot study were promising, particularly in the contexts where the intervention was delivered by nonprofessionals with no free medications and the proportion of unmotivated smokers was high in the study sample. Among the limited number published randomized trials targeting Asian American smokers, which included mostly smokers who were motivated to stop smoking such as callers to the quitline 32 or smokers who were willing to use NRT, 28-30 the 7-day abstinence rates of these trials ranged from 9.5% using LHW outreach 27 to 66% using intensive individual counseling sessions plus NRT at 3 months. 29 Only two of these trials provided 30-day or prolonged abstinence rates, which ranged from 15% with quitline 32 to 50% with intensive counseling plus NRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38,40 The abstinence rates obtained from this pilot study were promising, particularly in the contexts where the intervention was delivered by nonprofessionals with no free medications and the proportion of unmotivated smokers was high in the study sample. Among the limited number published randomized trials targeting Asian American smokers, which included mostly smokers who were motivated to stop smoking such as callers to the quitline 32 or smokers who were willing to use NRT, 28-30 the 7-day abstinence rates of these trials ranged from 9.5% using LHW outreach 27 to 66% using intensive individual counseling sessions plus NRT at 3 months. 29 Only two of these trials provided 30-day or prolonged abstinence rates, which ranged from 15% with quitline 32 to 50% with intensive counseling plus NRT.…”
Section: Discussionmentioning
confidence: 99%
“…Among the limited number published randomized trials targeting Asian American smokers, which included mostly smokers who were motivated to stop smoking such as callers to the quitline 32 or smokers who were willing to use NRT, 28-30 the 7-day abstinence rates of these trials ranged from 9.5% using LHW outreach 27 to 66% using intensive individual counseling sessions plus NRT at 3 months. 29 Only two of these trials provided 30-day or prolonged abstinence rates, which ranged from 15% with quitline 32 to 50% with intensive counseling plus NRT. 30 The findings showed that the SNFF intervention yielded comparable and promising quit rates for not only motivated but also for unmotivated smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large clinical trial conducted at the California quitline showed that Asian immigrant smokers readily use cessation counselling and successfully quit (Zhu et al, 2012). This is noteworthy because traditional counselling approaches with roots in Western psychology are often challenged on their applicability to an ever-changing, culturally diverse treatment-seeking clientele (Benish, Quintana & Wampold, 2011;Hwang, 2006;Sue, Zane, Nagayama Hall & Berger, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Only 24% of Korean American smokers in California had ever been advised to quit by a physician as opposed to 46% for the general population of smokers in the same state [5,6]. Recently several studies have been conducted to test the efficacy of a smoking cessation intervention in this group and some had positive cessation outcomes [7][8][9][10]. It has been argued that participants in a clinical trial of smoking cessation differ from the general population of smokers, which is often addressed as a major limitation of the study.…”
Section: Introductionmentioning
confidence: 99%